Piper Longum Carboxylase Oxygenase Inhibitor Protein Three Dimensional Structure Modelling and Ramachandran Plot Analysis (International Journal of Food and Nutritional Sciences, 2022)
Long pepper (Piper longum), also known as Indian long pepper or thippali, is produced for its fruit, which is dried and used as a spice and condiment. Long pepper tastes similar to Piper nigrum, which produces black, green, and white pepper, but it is spicier. This study seeks NCBI FASTA sequences for several proteins. BLAST is then used to find similar sequences. Swiss model modelled homology. The template model was created. This program's comparative modelling predicts protein sequence identification with 94.95% accuracy. The template protein's e value is 0.0, and chain A may score 990 for 100% similarity. Ramachandran plots verified the protein structure. Ramachandran plot analysis found 97% of residues in the desired locations. Other methods described and examined the projected 3D model.